Bridging the Spatiotemporal Gap in Diazotroph Activity and Diversity With High-Resolution Measurements - Benavides, Mar; Robidart, Julie (Frontiers in Marine Science, 2020)
The biological fixation of dinitrogen (N2) by marine microbes called ‘diazotrophs’ sustains ~50% of primary production in the ocean, boosting CO2 absorption by photoautotrophs and thus contributing to the mitigation of climate change. At present, the paucity and biased geographical coverage of N2 fixation and diazotroph diversity measurements impedes constraining nitrogen inputs to the ocean. Most studies have been conducted at very distant spatiotemporal scales, including: i) discrete and short duration measurements in small seawater volumes isolated from the environment, and ii) spatial extrapolations and global models of diazotrophy projected over decades to centuries. This knowledge gap lies at the fine scales: dynamic seawater structures <200 km wide and <2 months lifetime. However, the spatiotemporal resolution of conventional oceanographic cruises, with stations separated by tens to hundreds of kilometers, is too poor to resolve fine scale processes. Bridging this gap requires implementing high spatiotemporal resolution measurements. Here we present and discuss the advantages and disadvantages of contemporary methods and equipment able to provide high-resolution measurements at sea. We also provide insights into high-resolution sampling approaches to be developed in the near future. Increasing the spatiotemporal resolution of diazotroph activity and diversity will provide more realistic quantifications of nitrogen fluxes in the dynamic ocean.